Power lifting - Carey, Craig Robert; Mones, Isidre; Vazquez, Ivan (New York : Scholastic, 2006)
Describes powerful vehicles such as bulldozers, cargo planes, excavators, forklifts, and skidders.
Keywords: Construction equipment -- Juvenile literature; Motor vehicles -- Juvenile literature; Construction equipment; Motor vehicles